Anti-Migration and Invasion Effects of Astaxanthin against A172 Human Glioblastoma Cell Line - Tanapan Siangcham (2020)
OBJECTIVES: The study was to investigate anti-migration and invasion effects of astaxanthin (ATX), a natural carotenoid derivative distributed in marine environments, against A172 human glioblastoma cells. MATERIALS AND METHODS: Cell viability after ATX treatment was measured by MTT assays. Tumor cell migration and invasion were observed by scratch and Boyden chamber assays, respectively. Expression of MMP-2 and activity of MMP-9 were observed by immunoblotting and gelatin zymography, respectively. RESULTS: ATX up to 150 µM was not toxic to A172 cells at 48 h post-treatment. In contrast, ATX at 50 and 100 µM significantly decreased migration and invasion of A172 cells at 24 and 48 h post-treatment. Metastatic-reducing effect of ATX is associated with the reduction of MMP-2 and MMP-9 expressions in a dose-dependent manner. CONCLUSION: This finding indicated that ATX has anti-migration and invasion effects against human glioblastoma cells and might be applicable for the protection against metastasis of glioblastoma.